Does variation in trait schizotypy and frequency of cannabis use influence the acute subjective, cognitive and psychotomimetic effects of delta-9-tetrahydrocannabinol? A mega-analysis. (July 2021) - Freeman, Abigail M; Mokrysz, Claire; Hindocha, Chandni; Lawn, Will; Morgan, Celia JA; Freeman, Tom P; Saunders, Rob; Curran, H Valerie
Background: While the acute effects of cannabis are relatively benign for most users, some individuals experience significant adverse effects. This study aimed to identify whether variation in schizotypal personality traits and frequency of cannabis use influence the acute effects of delta-9-tetrahydrocannabinol (THC). Methods: Individual participant data from four double-blind, randomised, placebo-controlled, acute crossover studies involving 128 cannabis users were combined for a mega-analysis. Using multilevel linear models and moderation analyses, frequency of cannabis use and schizotypal personality traits were investigated as potential moderators of the subjective, cognitive and psychotomimetic effects of acute THC. Results: There was evidence of a moderating effect where increased frequency of cannabis use was associated with reduced intensity of subjective (changes in alertness and feeling stoned) and psychosis-like effects following THC when compared with placebo. Moderating effects of cannabis use frequency on acute memory impairment were weak. Trait schizotypy did not moderate the acute psychosis-like effects of THC compared with placebo. Conclusions: Our results suggest that a pattern of domain-specific tolerance develops to the acute effects of THC. Tolerance to the alertness-reducing effects occurred more readily than tolerance to psychotomimetic effects. Only partial tolerance to feeling stoned was found, and there was weak evidence for tolerance to memory impairment. Trait schizotypy did not moderate THC's effects on psychotomimetic symptoms.